Analyzing the UF resin distribution in particleboards by confocal laser scanning microscopy. (October 2019) - Altgen, Daniela; Grigsby, Warren; Altgen, Michael; Rautkari, Lauri; Mai, Carsten
Abstract: This study uses confocal laser scanning microscopy to analyze UF resin distribution within particleboards. Particleboards with three different resin contents were produced using a labeled UF resin. Furthermore, a plasma pre-treatment was applied to study the effect of an enhanced wettability of the particles on the resin distribution. With increasing resin content, the average resin spot size was increased and the distribution of resin areas shifted towards larger resin areas. Enhancing the wood wettability through plasma treatment had the opposite effect. Increased numbers of small resin areas was generated due to a better resin spreading and blending. The study further shows that confocal laser scanning microscopy allows qualitative investigations of resin within particleboards to determine differing resin locations and behaviors within and on particles.